2014
DOI: 10.1007/s11999-013-3164-7
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Femoral Nerve Block Using 0.125% Bupivacaine Does Not Prevent Early Ambulation After Total Knee Arthroplasty

Abstract: Background Continuous femoral nerve block has been shown to decrease opioid use, improve postoperative pain scores, and decrease length of stay. However, several studies have raised the concern that continuous femoral nerve block may delay patient ambulation and increase the risk of falls during the postoperative period. Questions/purposes This study sought to determine whether continuous femoral nerve block with a single-shot sciatic block prevented early ambulation after total knee arthroplasty (TKA) and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…But studies such as this one investigate data on anesthetic efficacy of the block for the intraoperative period, not analgesia for the postoperative period. There are studies which used 0.125% bupivacaine solution for infusion with FNB catheter and it's reported that this concentration does not prevent ambulation [15]. We believe a concentration as low as 0.125% bupivacaine for single shot FNB shows potential for early ambulation while maintaining adequate analgesia.…”
Section: Discussionmentioning
confidence: 86%
“…But studies such as this one investigate data on anesthetic efficacy of the block for the intraoperative period, not analgesia for the postoperative period. There are studies which used 0.125% bupivacaine solution for infusion with FNB catheter and it's reported that this concentration does not prevent ambulation [15]. We believe a concentration as low as 0.125% bupivacaine for single shot FNB shows potential for early ambulation while maintaining adequate analgesia.…”
Section: Discussionmentioning
confidence: 86%
“…First, the continuous femoral nerve blocks were performed with nerve stimulation rather than with ultrasound guidance [2,6]. Second, the concentration local anesthetic in the peripheral nerve blocks was 0.2-0.5% ropivacaine, as opposed to a lower dosage like 0.25% or even 0.125%, as reported by other authors [3,7]. Both of these factors could have contributed to the high rate of dysesthesia reported in the nerve block group.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Femoral nerve block (FNB) has been widely used due to its ease of application and its excellent pain relief after TKA [19][20][21][22][23][24][25], while concerned with weakens quadriceps strength [26,27] due to blocking the proximal femoral nerve which contains both motor and sensory fibers [28]. As the alternative, adductor canal block (ACB) can provide equally effective pain relief preserving quadriceps strength [29][30][31][32], because the blocking the nerve distally to that of the FNB can anesthetize only the purely sensory saphenous nerve in the adductor canal [26,27,33].…”
Section: Introductionmentioning
confidence: 99%